Marked inductor and marked laminated sheet

Marked inductors and laminated sheets with visible marks on a magnetic layer address the challenges of inaccurate alignment and lack of product information in existing inductor technologies, providing a solution for precise alignment and information retrieval.

JP2025063276AInactive Publication Date: 2025-04-15NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025009323
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-17
Filing Date
2025-01-22
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing inductors lack accurate alignment methods for forming vias and do not provide necessary product information to users before installation.

Method used

The development of marked inductors and marked laminated sheets, which feature a magnetic layer with buried wirings and visible marks on one side, allowing for precise alignment and information retrieval.

Benefits of technology

Enables accurate alignment of inductors for via formation and reliable acquisition of product information, enhancing the installation process and user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025063276000001_ABST
    Figure 2025063276000001_ABST
Patent Text Reader

Abstract

To provide a marked inductor and a marked laminated sheet that can form vias by performing alignment with high precision, or can reliably obtain information about products.SOLUTION: A marked inductor 21 includes a sheet-shaped inductor 2 having a plurality of wires 7 and a magnetic layer 8 in which the plurality of wires 7 are embedded, and a mark 4 arranged on one side in the thickness direction of the inductor 2 and / or formed on the magnetic layer 8.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a marked inductor and a marked laminated sheet. [Background technology]

[0002] Conventionally, it is known that sheet-shaped inductors are mounted in electronic devices. For example, an inductor including a wiring and a magnetic layer covering the wiring has been proposed (for example, see Patent Document 1 below). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-220618 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, in some cases, vias are formed in the magnetic layer to electrically connect the wiring to an electronic device. In this case, it is necessary to align the inductor in order to accurately recognize the position of the wiring in a plan view. However, the technique disclosed in Patent Document 1 has a problem in that the inductor cannot be aligned with high precision.

[0005] Furthermore, there is a demand from users to obtain information about inductors to be mounted in electronic devices before mounting them. However, the inductor in Patent Document 1 does not include the above-mentioned information. This causes a problem in that users cannot obtain the inductor information in advance.

[0006] The present invention provides a marked inductor and a marked laminated sheet that can form vias with high alignment accuracy or reliably obtain information about a product. [Means for solving the problem]

[0007] The present invention (1) includes a sheet-shaped inductor having a plurality of wirings and a magnetic layer in which the plurality of wirings are embedded, and a marked inductor arranged on one side in a thickness direction of the inductor and / or formed on the magnetic layer.

[0008] Since the marked inductor includes a mark, it is possible to align the marked inductor based on the mark to form a via, or to recognize information about the product based on the mark, and to reliably obtain such information.

[0009] The present invention (2) includes the inductor with a mark according to (1), in which the mark is spaced apart from the wiring when projected in the thickness direction.

[0010] In this inductor with marks, the marks are spaced apart from the wiring. In other words, the marks are not disposed facing one side of the wiring in the thickness direction. Therefore, the marks are formed without misalignment due to the presence of the wiring. This allows the inductor with marks to be aligned more accurately, and also allows information about the product to be obtained more reliably.

[0011] The present invention (3) includes a marked laminate sheet as described in (1) or (2), comprising a marked inductor in which the mark is arranged on one side of the inductor in a thickness direction, and a mark layer arranged on one surface of the inductor in the thickness direction, on which the mark is arranged.

[0012] Since this marked laminate sheet has marks, it is possible to align the marked laminate sheet based on the marks to form vias, or to recognize information about the product based on the marks and reliably obtain such information.

[0013] Furthermore, since the marked laminate sheet includes a mark layer, the mark can be reliably provided.

[0014] The present invention (4) includes the marked laminate sheet according to (3), in which the material of the mark layer is a resin composition.

[0015] In this marked laminate sheet, the mark layer is made of a resin composition, so that the marks can be easily formed.

[0016] The present invention (5) includes the marked laminate sheet according to (4), wherein the resin composition is a thermosetting resin composition and satisfies at least one of the following tests (a) to (e):

[0017] Test (a): The marked laminated sheet is cut into a 3 cm square to prepare a sample, and its relative permeability μ1 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of copper sulfate plating solution containing 66 g / L copper sulfate pentahydrate, 180 g / L sulfuric acid, 50 ppm chlorine, and top lutina α at 25°C for 120 minutes, and then the relative permeability μ2 at a frequency of 10 MHz of the sample is determined. The rate of change in permeability before and after immersion is determined using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0018] Permeability change rate (%) = |μ1-μ2| / μ1×100 Test (b): The marked laminated sheet is cut into a 3 cm square to prepare a sample, and its relative permeability μ3 at a frequency of 10 MHz is measured. The sample is then immersed in 200 mL of an acid activation aqueous solution containing 55 g / L of sulfuric acid at 25°C for 1 minute, and the relative permeability μ4 at a frequency of 10 MHz is then measured. The rate of change in permeability before and after immersion is calculated using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0019] Permeability change rate (%) = |μ3-μ4| / μ3×100 Test (c): The laminated sheet with the mark is cut into a 3 cm square to prepare a sample, and its relative permeability μ5 at a frequency of 10 MHz is measured. The sample is then immersed in 200 mL of Reduction Solution Securigant P manufactured by Atotech Japan at 45°C for 5 minutes, and the relative permeability μ6 at a frequency of 10 MHz is then measured. The rate of change in magnetic permeability before and after immersion is calculated using the following formula: As a result, the rate of change in magnetic permeability of the sample is 5% or less.

[0020] Permeability change rate (%) = |μ5-μ6| / μ5×100 Test (d): The laminated sheet with the mark is cut into a 3 cm square to prepare a sample, and its relative permeability μ7 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of Concentrate Compact CP manufactured by Atotech Japan at 80°C for 15 minutes, and the relative permeability μ8 at a frequency of 10 MHz of the sample is then determined. The rate of change in permeability before and after immersion is determined using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0021] Permeability change rate (%) = |μ7-μ8| / μ7×100 Test (e): The laminated sheet with the mark is cut into a 3 cm square to prepare a sample, and its relative permeability μ9 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of Swelling Dip Securigant P manufactured by Atotech Japan at 60°C for 5 minutes, and the relative permeability μ10 at a frequency of 10 MHz is then determined. The rate of change in permeability before and after immersion is determined using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0022] Permeability change rate (%) = |μ9-μ10| / μ9×100 This marked laminate sheet satisfies at least one of tests (a) to (e), and therefore has excellent stability against processing using chemicals.

[0023] The present invention (6) includes the inductor with mark according to (1), in which the mark is a through hole that penetrates the magnetic layer in the thickness direction.

[0024] In this inductor with marks, visibility from the other side in the thickness direction can be ensured even if an insulating layer is disposed on the magnetic layer. Effect of the Invention

[0025] The marked inductor and the marked laminated sheet of the present invention can form vias with high alignment accuracy, or can reliably obtain information about a product. [Brief description of the drawings]

[0026] [Figure 1] 1A to 1C are plan views of the manufacturing process of one embodiment of the marked laminate sheet of the present invention, where FIG. 1A is a laminate sheet, FIG. 1B is a marked laminate sheet, and FIG. 1C is a marked laminate sheet in which a via is formed. [Diagram 2] 2A to 2D are front cross-sectional views of the manufacturing process of one embodiment of the marked laminate sheet of the present invention, where FIG. 2A is an inductor, FIG. 2B is a laminate sheet, FIG. 2C is a marked laminate sheet, and FIG. 2D is a marked laminate sheet in which a via is formed. [Diagram 3] FIG. 3 is an enlarged cross-sectional view of a modified example of the mark of the marked laminate sheet shown in FIG. 2C. [Figure 4] FIG. 4 is an enlarged cross-sectional view of a modified example of the mark of the marked laminate sheet shown in FIG. 2C. [Diagram 5] FIG. 5 is an enlarged cross-sectional view of a modified example of the mark of the marked laminate sheet shown in FIG. 2C. [Figure 6] FIG. 6 is a front cross-sectional view of one embodiment of a marked inductor of the present invention. [Figure 7] FIG. 7 is a plan view of a modified example of the marked inductor shown in FIG. [Figure 8] FIG. 8 is a plan view of a modified example of the marked inductor shown in FIG. [Figure 9]FIG. 9 is a plan view of a modified example of the marked laminate sheet shown in FIG. 1B (a modified example in which the mark is a lot number). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] <One embodiment> One embodiment of the marked laminate sheet of the present invention will be described with reference to Figures 1B and 2C.

[0028] The laminated sheet 1 with the mark has a predetermined thickness and a sheet shape extending in a plane direction perpendicular to the thickness direction. For example, the laminated sheet 1 with the mark has a generally rectangular shape in a plan view. The laminated sheet 1 with the mark includes a sheet-like inductor 2, a mark layer 3, and a mark 4.

[0029] The inductor 2 has the same outer shape as the marked laminated sheet 1 in a plan view. Specifically, the inductor 2 has a substantially rectangular shape including four sides 5 in a plan view.

[0030] The inductor 2 also includes a plurality of wirings 7 and a magnetic layer 8.

[0031] The multiple wirings 7 are adjacent to each other with a gap therebetween. The multiple wirings 7 are parallel to each other. The multiple wirings 7 extend along a direction perpendicular to the adjacent direction and the thickness direction. The shape, dimensions, configuration, material, formulation (filling rate, content ratio, etc.) of the wirings 7 are described, for example, in JP 2019-220618 A. Preferably, the wirings 7 are substantially circular in a cross section along a direction perpendicular to the direction along the wirings 7, and the lower limit of the diameter is, for example, 25 μm, and the upper limit of the diameter is, for example, 2,000 μm. The wirings 7 preferably include a conductor wire and an insulating film that covers the circumferential surface of the conductor wire. The lower limit of the interval between adjacent wirings 7 is, for example, 10 μm, preferably 50 μm, and the upper limit of the interval between adjacent wirings 7 is, for example, 5,000 μm, preferably 3,000 μm. The upper limit of the ratio of the diameter of the wiring 7 to the interval between adjacent wirings 7 (diameter / interval) is, for example, 200, or preferably 50, and the lower limit is, for example, 0.01, or preferably 0.1.

[0032] The magnetic layer 8 improves the inductance of the laminated sheet 1 with a mark. The magnetic layer 8 has the same outer shape as the inductor 2 in a plan view. The magnetic layer 8 has a plate shape extending in the planar direction. In addition, the magnetic layer 8 has a plurality of wirings 7 embedded therein in a cross-sectional view. The magnetic layer 8 has one surface 9, the other surface 10, and an inner peripheral surface 11.

[0033] One surface 9 forms one surface of the magnetic layer 8 in the thickness direction.

[0034] The other surface 10 forms the other surface in the thickness direction of the magnetic layer 8. The other surface 10 is spaced apart from the one surface 9 on the other side in the thickness direction.

[0035] The inner circumferential surface 11 is spaced apart from the one surface 9 and the other surface 10 in the thickness direction. The inner circumferential surface 11 is located between the one surface 9 and the other surface 10 in the thickness direction. The inner circumferential surface 11 is also located between two opposing outer surface 18 in the direction in which the multiple wirings 7 are adjacent to each other. The inner circumferential surface 11 contacts the outer circumferential surfaces of the wirings 7.

[0036] The magnetic layer 8 includes a binder and magnetic particles. Specifically, the material of the magnetic layer 8 is a magnetic composition containing a binder and magnetic particles.

[0037] Examples of the binder include thermoplastic resins such as acrylic resins, and thermosetting resins such as epoxy resin compositions. The acrylic resins include, for example, carboxyl-containing acrylic acid ester copolymers. The epoxy resin compositions include, for example, an epoxy resin (such as cresol novolac epoxy resin) as a base, a curing agent for epoxy resins (such as phenolic resins), and a curing accelerator for epoxy resins (such as imidazole compounds). As the binder, a thermoplastic resin and a thermosetting resin can be used alone or in combination, and preferably a thermoplastic resin and a thermosetting resin are used in combination. The volume ratio of the binder in the magnetic composition is the remainder of the volume ratio of the magnetic particles described below.

[0038] The magnetic particles are dispersed in, for example, a binder. In this embodiment, the magnetic particles have, for example, a substantially flat shape. Note that the substantially flat shape includes a substantially plate shape. Note that the magnetic particles may have a substantially spherical shape or a substantially needle shape. Preferably, the magnetic particles have a substantially flat shape.

[0039] When the magnetic particles have a substantially flat shape, the lower limit of the flatness (degree of flatness) is, for example, 8, preferably 15, and the upper limit is, for example, 500, preferably 450. The flatness is calculated, for example, as the aspect ratio obtained by dividing the median diameter of the magnetic particles by the average thickness of the magnetic particles.

[0040] The lower limit of the median diameter of the magnetic particles is, for example, 3.5 μm, preferably 10 μm, and the upper limit is, for example, 200 μm, preferably 150 μm. When the magnetic particles have a substantially flat shape, the lower limit of the average thickness is, for example, 0.1 μm, preferably 0.2 μm, and the upper limit is, for example, 3.0 μm, preferably 2.5 μm.

[0041] The material of the magnetic particles is a metal. Examples of the metal include magnetic materials such as soft magnetic materials and hard magnetic materials. From the viewpoint of ensuring good inductance, a soft magnetic material is preferable.

[0042] Examples of soft magnetic bodies include single metal bodies that contain one type of metal element in a pure substance state, and alloy bodies that are eutectic bodies (mixtures) of one or more types of metal elements (first metal elements) and one or more types of metal elements (second metal elements) and / or nonmetal elements (carbon, nitrogen, silicon, phosphorus, etc.). These can be used alone or in combination.

[0043] The single metal body may be, for example, a metal element consisting of only one type of metal element (first metal element). The first metal element may be, for example, iron (Fe), cobalt (Co), nickel (Ni), or any other metal element that can be contained as the first metal element in a soft magnetic body.

[0044] In addition, the single metal body may be, for example, a form including a core containing only one type of metal element and a surface layer containing an inorganic and / or organic substance that modifies a part or the whole of the surface of the core, such as a form in which an organometallic compound or an inorganic metal compound containing a first metal element is decomposed (e.g., thermally decomposed). More specifically, the latter form may be iron powder (sometimes called carbonyl iron powder) obtained by thermally decomposing an organoiron compound (specifically, carbonyl iron) containing iron as the first metal element. The position of the layer containing an inorganic and / or organic substance that modifies the part containing only one type of metal element is not limited to the surface as described above. The organometallic compound or inorganic metal compound that can obtain the single metal body is not particularly limited, and can be appropriately selected from known or commonly used organometallic compounds or inorganic metal compounds that can obtain a single metal body of a soft magnetic material.

[0045] The alloy body is a eutectic of one or more metal elements (first metal elements) and one or more metal elements (second metal elements) and / or non-metallic elements (carbon, nitrogen, silicon, phosphorus, etc.), and is not particularly limited as long as it can be used as an alloy body of a soft magnetic material.

[0046] The first metallic element is an essential element in the alloy body, and examples of the first metallic element include iron (Fe), cobalt (Co), nickel (Ni), etc. If the first metallic element is Fe, the alloy body is an Fe-based alloy, if the first metallic element is Co, the alloy body is a Co-based alloy, and if the first metallic element is Ni, the alloy body is a Ni-based alloy.

[0047] The second metallic element is an element (secondary component) secondarily contained in the alloy body, and is a metallic element that is compatible (eutectic) with the first metallic element, and examples of the second metallic element include iron (Fe) (when the first metallic element is other than Fe), cobalt (Co) (when the first metallic element is other than Co), nickel (Ni) (when the first metallic element is other than Ni), chromium (Cr), aluminum (Al), silicon (Si), copper (Cu), silver (Ag), manganese (Mn), calcium (Ca), barium (Barium), and the like. Ba, titanium (Ti), zirconium (Zr), hafnium (Hf), vanadium (V), niobium (Nb), tantalum (Ta), molybdenum (Mo), tungsten (W), ruthenium (Ru), rhodium (Rh), zinc (Zn), gallium (Ga), indium (In), germanium (Ge), tin (Sn), lead (Pb), scandium (Sc), yttrium (Y), strontium (Sr), various rare earth elements, etc. These can be used alone or in combination of two or more.

[0048] The nonmetallic element is an element (secondary component) secondarily contained in the alloy body, and is a nonmetallic element that is compatible (eutectic) with the first metallic element, such as boron (B), carbon (C), nitrogen (N), silicon (Si), phosphorus (P), sulfur (S), etc. These may be used alone or in combination of two or more kinds.

[0049] Examples of the alloy body include Fe-based alloys, such as magnetic stainless steel (Fe-Cr-Al-Si alloy) (including electromagnetic stainless steel), Sendust (Fe-Si-Al alloy) (including super Sendust), Permalloy (Fe-Ni alloy), Fe-Ni-Mo alloy, Fe-Ni-Mo-Cu alloy, Fe-Ni-Co alloy, Fe-Cr alloy, Fe-Cr-Al alloy, Fe-Ni-Cr alloy, Fe-Ni-Cr-Si alloy, silicon copper (Fe-Cu-Si alloy), Fe-Si alloy, Fe-Si-B(-Cu-Nb) alloy, Fe-B-Si-Cr alloy, Fe-S Examples of such alloys include i-Cr-Ni alloys, Fe-Si-Cr alloys, Fe-Si-Al-Ni-Cr alloys, Fe-Ni-Si-Co alloys, Fe-N alloys, Fe-C alloys, Fe-B alloys, Fe-P alloys, ferrites (including stainless steel ferrites, and soft ferrites such as Mn-Mg ferrites, Mn-Zn ferrites, Ni-Zn ferrites, Ni-Zn-Cu ferrites, Cu-Zn ferrites, and Cu-Mg-Zn ferrites), permendur (Fe-Co alloys), Fe-Co-V alloys, and Fe-based amorphous alloys.

[0050] Examples of the alloy body, which is a Co-based alloy, include Co-Ta-Zr and cobalt (Co)-based amorphous alloys.

[0051] An example of the alloy body is a Ni-based alloy, such as a Ni-Cr alloy.

[0052] A more detailed formulation of the above-mentioned magnetic composition is described in, for example, JP-A-2014-165363.

[0053] The lower limit of the volume fraction of the magnetic particles in the magnetic composition is, for example, 40 volume %, preferably 50 volume %, more preferably 60 volume %, and the upper limit is, for example, 95 volume %, preferably 90 volume %.

[0054] The lower limit of the thickness of the inductor 2 is, for example, 30 μm, or preferably 40 μm, and the upper limit of the thickness of the inductor 2 is, for example, 2,500 μm, or preferably 2,000 μm.

[0055] The lower limit of the ratio of the thickness of the inductor 2 to the thickness of the marked laminated sheet 1 is, for example, 0.1, preferably 0.3, more preferably 0.7, and the upper limit is, for example, 0.999, preferably 0.990, more preferably 0.980.

[0056] The mark layer 3 is a layer on which the marks 4 described below are formed. The mark layer 3 has a sheet shape extending in the surface direction. Specifically, the mark layer 3 has the same outer shape as the marked laminated sheet 1 in a plan view. The mark layer 3 is disposed on one surface 9 of the magnetic layer 8. Specifically, the mark layer 3 is in contact with the entire one surface 9.

[0057] The material of the mark layer 3 is not particularly limited and may be, for example, a resin composition, a metal, a ceramic, or the like, and is preferably a resin composition. If the material of the mark layer 3 is a resin composition, it is easy to form the mark 4 described below.

[0058] The resin composition contains, for example, a resin as an essential component, and particles as an optional component.

[0059] Examples of the resin include curable resins such as thermosetting resins and active energy ray curable resins, and plastic resins such as thermoplastic resins.

[0060] The curable resin is preferably a thermosetting resin, which contains a base resin, a curing agent, and a curing accelerator.

[0061] Examples of the base resin include epoxy resins and silicone resins, and preferably epoxy resins. Examples of the epoxy resin include bifunctional epoxy resins such as bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, modified bisphenol A type epoxy resins, modified bisphenol F type epoxy resins, modified bisphenol S type epoxy resins, and biphenyl type epoxy resins, and polyfunctional epoxy resins having three or more functional groups such as phenol novolac type epoxy resins, cresol novolac type epoxy resins, trishydroxyphenylmethane type epoxy resins, tetraphenylolethane type epoxy resins, and dicyclopentadiene type epoxy resins. These epoxy resins can be used alone or in combination of two or more kinds. Preferably, bifunctional epoxy resins are used, and more preferably, bisphenol A type epoxy resins are used.

[0062] The lower limit of the epoxy equivalent of the epoxy resin is, for example, 10 g / eq., and the upper limit is, for example, 1,000 g / eq.

[0063] If the main agent is an epoxy resin, the curing agent may be, for example, a phenol resin or an isocyanate resin. The phenol resin may be, for example, a polyfunctional phenol resin such as a phenol novolac resin, a cresol novolac resin, a phenol aralkyl resin, a phenol biphenylene resin, a dicyclopentadiene type phenol resin, or a resol resin. These may be used alone or in combination of two or more. The phenol resin may preferably be a phenol novolac resin or a phenol biphenylene resin. If the main agent is an epoxy resin and the curing agent is a phenol resin, the lower limit of the total of the hydroxyl groups in the phenol resin relative to 1 equivalent of the epoxy group in the epoxy resin is, for example, 0.7 equivalents, preferably 0.9 equivalents, and the upper limit is, for example, 1.5 equivalents, preferably 1.2 equivalents. Specifically, the lower limit of the mass parts of the curing agent is, for example, 1 part by mass, or, for example, 50 parts by mass, relative to 100 parts by mass of the main agent.

[0064] The curing accelerator is a catalyst (thermosetting catalyst) (preferably an epoxy resin curing accelerator) that accelerates the curing of the base agent, and examples thereof include organic phosphorus compounds, such as imidazole compounds such as 2-phenyl-4-methyl-5-hydroxymethylimidazole (2P4MHZ). The lower limit of the number of parts by mass of the curing accelerator is, for example, 0.05 parts by mass, and the upper limit is, for example, 5 parts by mass, relative to 100 parts by mass of the base agent.

[0065] Examples of the thermoplastic resin include acrylic resin, polyester resin, thermoplastic polyurethane resin, etc. Examples of the thermoplastic resin also include hydrophilic polymers.

[0066] As the resin, either a hardening resin or a plastic resin can be used alone, or they can be used in combination.

[0067] The lower limit of the mass proportion of the resin in the resin composition is, for example, 10 mass%, preferably 30 mass%, and the upper limit is, for example, 90 mass%, preferably 75 mass%.

[0068] The particles are at least one type selected from the group consisting of first particles and second particles.

[0069] The first particles have, for example, a substantially spherical shape. The lower limit of the median diameter of the first particles is, for example, 1 μm, preferably 5 μm, and the upper limit of the median diameter of the first particles is, for example, 250 μm, preferably 200 μm. The median diameter of the first particles is determined by a laser diffraction particle size distribution measuring device. The median diameter of the first particles can also be determined, for example, by binarization processing based on cross-sectional observation.

[0070] The material of the first particles is not particularly limited. Examples of the material of the first particles include metals, inorganic compounds, organic compounds, and simple nonmetallic elements, and from the viewpoint of reliably forming the mark 4, inorganic compounds and simple nonmetallic elements are preferable.

[0071] The inorganic compound is contained in the resin composition when the mark layer 3 functions as an ink receiving layer. Examples of the inorganic compound include inorganic fillers, specifically, silica and alumina, and preferably, silica.

[0072] The nonmetallic element is contained in the resin composition when the mark layer 3 functions as a laser discoloration layer. Examples of the nonmetallic element include carbon and silicon, preferably carbon, and more preferably carbon black.

[0073] Specifically, as the first particles, preferably, spherical silica is used, and also preferably, spherical carbon black is used.

[0074] The second particles have, for example, a substantially flat shape. The substantially flat shape includes a substantially plate shape.

[0075] The lower limit of the flattening ratio (flatness) of the second particles is, for example, 8, or preferably 15, and the upper limit is, for example, 500, or preferably 450. The flattening ratio of the second particles is calculated by the same method as the flattening ratio of the magnetic particles in the magnetic layer 8 described above.

[0076] The lower limit of the median diameter of the second particles is, for example, 1 μm, or preferably 5 μm, and the upper limit of the median diameter of the second particles is, for example, 250 μm, or preferably 200 μm. The median diameter of the second particles is determined in the same manner as that of the first particles.

[0077] The lower limit of the average thickness of the second particles is, for example, 0.1 μm, preferably 0.2 μm, and the upper limit is, for example, 3.0 μm, preferably 2.5 μm.

[0078] The material of the second particles is an inorganic compound, such as a thermally conductive compound such as boron nitride.

[0079] Specifically, the second particles are preferably flat-shaped boron nitride particles.

[0080] The resin composition may contain a single type of the first particles and a single type of the second particles, or may contain both of them.

[0081] The lower limit of the number of parts by mass of the particles (first particles and / or second particles) relative to 100 parts by mass of the resin is, for example, 10 parts by mass, preferably 50 parts by mass, and the upper limit is, for example, 2,000 parts by mass, preferably 1,500 parts by mass. The lower limit of the content ratio of the particles in the resin composition is, for example, 10% by mass, and the upper limit is, for example, 90% by mass. When both the first particles and the second particles are included in the resin composition, the lower limit of the number of parts by mass of the second particles relative to 100 parts by mass of the first particles is, for example, 30 parts by mass, and the upper limit is, for example, 300 parts by mass.

[0082] In addition, since the particles are an optional component in the resin composition, the resin composition does not necessarily need to contain particles.

[0083] The lower limit of the thickness of the mark layer 3 is, for example, 1 μm, preferably 10 μm, and the upper limit is, for example, 1,000 μm, preferably 100 μm. The lower limit of the ratio of the thickness of the mark layer 3 to the thickness of the marked laminated sheet 1 is, for example, 0.001, preferably 0.005, more preferably 0.01, and the upper limit is, for example, 0.5, preferably 0.3, more preferably 0.1.

[0084] The marks 4 are, for example, marks that notify positional information of the multiple wirings 7 in the inductor 2. The marks 4 are also alignment marks for forming the vias 16 in the laminated sheet 1 with the marks.

[0085] The marks 4 are formed on the mark layer 3. Specifically, the marks 4 are disposed on one surface in the thickness direction of the mark layer 3. For example, each of the marks 4 is formed in each of four corners 6 defined by four sides 5 of the mark layer 3. The marks 4 have, for example, a substantially cross shape in plan view.

[0086] The mark 4 is a recess extending from one surface in the thickness direction of the mark layer 3 toward the other surface in the thickness direction, and proceeds partway in the thickness direction.

[0087] Furthermore, when projected in the thickness direction, the mark 4 is separated from the plurality of wirings 7 on the outer side in the adjacent direction. In other words, when projected in the thickness direction, the mark 4 does not overlap with the plurality of wirings 7, but is shifted from the plurality of wirings 7. The minimum distance L between the mark 4 and the wirings 7 has a lower limit of, for example, 10 μm, or preferably 50 μm, and an upper limit of, for example, 10 mm, or preferably 5 mm, or more preferably 3 mm.

[0088] The dimensions of the mark 4 are not particularly limited. The lower limit of the length of the mark 4 in the direction in which the wiring 7 extends is, for example, 10 μm, preferably 50 μm, more preferably 300 μm, and the upper limit is, for example, 5 mm, preferably 2 mm, more preferably 1 mm. The lower limit of the length of the mark 4 in the direction in which the multiple wirings 7 are adjacent to each other is, for example, 10 μm, preferably 50 μm, more preferably 300 μm, and the upper limit is, for example, 5 mm, preferably 2 mm, more preferably 1 mm. If the above-mentioned dimensions of the mark 4 are equal to or greater than the above-mentioned lower limit, the mark 4 can be reliably read as an alignment mark. If the above-mentioned dimensions of the mark 4 are equal to or less than the above-mentioned upper limit, the marked laminated sheet 1 can be made small.

[0089] The lower limit of the depth of the mark 4 is, for example, 1 μm, or preferably 5 μm, and the upper limit is 1 mm. The lower limit of the ratio of the depth of the mark 4 to the thickness (depth) of the mark layer 3 is, for example, 0.01, or preferably 0.1, and the upper limit is, for example, 0.9, or preferably 0.7.

[0090] Next, a method for producing and processing the above-mentioned marked laminated sheet 1 will be described with reference to FIGS. 1A to 2D.

[0091] In this method, first, as shown in Fig. 2A, an inductor 2 is prepared. The inductor 2 is prepared by, for example, a method described in JP 2019-220618 A or the like.

[0092] Next, in this method, as shown in FIGS. 1A and 2B, a mark-formable layer 15 is disposed on one surface of the inductor 2 in the thickness direction.

[0093] The mark-formable layer 15 is a layer on which the mark 4 has not yet been provided, and on which the mark 4 can be formed in the next step. The material of the mark-formable layer 15 is the same as the material of the mark layer 3. To place the mark-formable layer 15 on the inductor 2, first, the mark-formable sheet 14 is prepared. The mark-formable sheet 14 is a sheet before the mark-formable layer 15 is placed on one side 9 of the inductor 2, and its material is the same as the material of the mark layer 3. To prepare the mark-formable sheet 14, a solvent is further mixed with the above-mentioned material to prepare a varnish, which is applied to the surface of a release sheet (not shown) and dried. When the resin contains a thermosetting resin, the thermosetting resin is in the B stage or C stage.

[0094] Next, the mark-formable sheet 14 is attached to one thickness-wise surface of the inductor 2. Specifically, the other thickness-wise surface of the mark-formable sheet 14 is brought into contact with one thickness-wise surface of the inductor 2. As a result, the mark-formable sheet 14 is formed on the mark-formable layer 15 in a state of contacting the one surface 9.

[0095] Thereafter, if the resin contains a B-stage thermosetting resin, the thermosetting resin is converted to a C-stage by heating.

[0096] As a result, the mark-formable layer 15 is disposed (laminated) on one surface in the thickness direction of the inductor 2. Preferably, the mark-formable layer 15 is adhered to one surface 9 of the magnetic layer 8.

[0097] This produces a laminated sheet 13 including the inductor 2 and the mark-formable layer 15. This laminated sheet 13 does not yet include the mark 4, is a component for producing the marked laminated sheet 1, is a device that can be distributed independently, and is industrially applicable.

[0098] The method then proceeds to form marks 4 in the markable layer 15, as shown in Figures 1B and 2C.

[0099] The method for forming the marks 4 is not particularly limited, and examples thereof include punching with a drill or shear, physical polishing (eg, sandblasting, etc.), and chemical etching.

[0100] As a result, the mark-formable layer 15 becomes the mark layer 3 on which the marks 4 are formed. In this way, a laminated sheet 1 with marks, which is provided with the inductor 2, the mark layer 3, and the marks 4, is obtained.

[0101] The marked laminate sheet 1 satisfies at least one of the tests (a) to (e), for example.

[0102] Test (a): A sample is prepared by cutting the marked laminated sheet 1 into a 3 cm square shape, and its relative permeability μ1 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of copper sulfate plating solution containing 66 g / L copper sulfate pentahydrate, 180 g / L sulfuric acid concentration, 50 ppm chlorine, and Top Lutina α manufactured by Okuno Chemical Industries Co., Ltd. at 25°C for 120 minutes, and then the relative permeability μ2 of the sample at a frequency of 10 MHz is determined. The rate of change in permeability before and after immersion is calculated using the following formula. As a result, the rate of change in the magnetic permeability of the sample is 5% or less.

[0103] Permeability change rate (%) = |μ1-μ2| / μ1×100 Test (b): A sample is made by cutting the marked laminated sheet 1 into a 3 cm square, and its relative permeability μ3 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of an acid activation aqueous solution containing 55 g / L of sulfuric acid at 25°C for 1 minute, and then the relative permeability μ4 of the sample at a frequency of 10 MHz is determined. The rate of change in permeability before and after immersion is calculated using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0104] Permeability change rate (%) = |μ3-μ4| / μ3×100 Test (c): The marked laminated sheet 1 is cut into a 3 cm square to prepare a sample, and its relative permeability μ5 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of Atotech Japan's Reduction Solution Securigant P at 45°C for 5 minutes, and the relative permeability μ6 at a frequency of 10 MHz is then determined. The rate of change in permeability before and after immersion is determined using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0105] Permeability change rate (%) = |μ5-μ6| / μ5×100 Test (d): A sample is made by cutting the marked laminated sheet 1 into a 3 cm square shape, and its relative permeability μ7 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of Concentrate Compact CP manufactured by Atotech Japan at 80°C for 15 minutes, and the relative permeability μ8 of the sample at a frequency of 10 MHz is then determined. The rate of change in permeability before and after immersion is calculated using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0106] Permeability change rate (%) = |μ7-μ8| / μ7×100 Test (e): A sample is made by cutting the marked laminated sheet 1 into a 3 cm square shape, and its relative permeability μ9 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of Swelling Dip Securigant P manufactured by Atotech Japan at 60°C for 5 minutes, and the relative permeability μ10 of the sample at a frequency of 10 MHz is then determined. The rate of change in permeability before and after immersion is calculated using the following formula. As a result, the rate of change in the sample's permeability is 5% or less.

[0107] Permeability change rate (%) = |μ9-μ10| / μ9×100 In the case where test (a) is satisfied, the upper limit of the percent change in magnetic permeability of the sample in test (a) is preferably 4%, more preferably 3%.

[0108] If the test (a) is satisfied, the marked laminate sheet 1 has excellent stability against immersion in a copper sulfate solution for electrolytic copper plating.

[0109] In the case where test (b) is satisfied, the upper limit of the percentage change in magnetic permeability of the sample in test (b) is preferably 4%, more preferably 3%.

[0110] If the test (b) is satisfied, the marked laminate sheet 1 has excellent stability against immersion in an acid activation solution.

[0111] In the case where test (c) is satisfied, the upper limit of the percent change in magnetic permeability of the sample in test (c) is preferably 4%, more preferably 3%.

[0112] In test (c), Reduction Solution Securiganth P manufactured by Atotech Japan Ltd. contains an aqueous sulfuric acid solution and is used as a neutralizing liquid (neutralizing agent or aqueous solution for neutralization). Therefore, if test (c) is satisfied, the marked laminated sheet 1 has excellent stability against immersion in a neutralizing liquid.

[0113] In the case where test (d) is satisfied, the upper limit of the percent change in magnetic permeability of the sample in test (d) is preferably 4%, more preferably 3%.

[0114] The Concentrate Compact CP manufactured by Atotech Japan in test (d) contains a potassium permanganate solution. Therefore, if test (d) is satisfied, the marked laminated sheet 1 has excellent stability against immersion in a potassium permanganate solution for desmear (cleaning).

[0115] In the case where test (e) is satisfied, the upper limit of the percent change in magnetic permeability of the sample in test (e) is preferably 4%, more preferably 3%.

[0116] In the test (e), Swelling Dip Securigant P manufactured by Atotech Japan is an aqueous solution containing glycol ethers and sodium hydroxide, and is used as the swelling liquid. Therefore, if the test (e) is satisfied, the marked laminated sheet 1 has excellent stability against immersion in a swelling liquid.

[0117] Preferably, all of tests (a) to (e) are satisfied. Therefore, the marked laminate sheet 1 has excellent stability against immersion in a copper sulfate solution for electrolytic copper plating, an acid activation solution, a neutralizing solution, a potassium permanganate solution for desmearing (cleaning), and a swelling solution, and has excellent stability against various processes using these solutions.

[0118] As shown in Figures 1C and 2D, vias 16 are then formed in the marked laminate sheet 1.

[0119] In forming the vias 16, for example, the mark 4 is used as an alignment mark to align the marked laminated sheet 1. For example, the mark 4 (its position) is recognized (read) by a recognition device arranged on one side in the thickness direction of the marked laminated sheet 1, and the mark 4 is used as a reference to adjust the surface direction position of the marked laminated sheet 1 with respect to the device that will perform the next processing.

[0120] The method for forming the vias 16 is not particularly limited, and examples thereof include contact opening such as drilling and sandblasting, and non-contact processing such as using a laser.

[0121] For example, the via 16 overlaps with the wiring 7 in a plan view. More specifically, the via 16 is a through hole that exposes the center of one surface of the wiring 7 in the thickness direction and penetrates the magnetic layer 8 and the mark layer 3 located on one side of the wiring 7 in the thickness direction in the thickness direction. The via 16 has a substantially circular shape in a plan view (not shown). In addition, the via 16 has a tapered shape in a cross-sectional view, in which the opening area increases toward one side in the thickness direction. Alternatively, although not shown, the via 16 may have a straight shape in a cross-sectional view, in which the opening cross-sectional area is the same on one side in the thickness direction.

[0122] Thereafter, the laminated sheet 1 with the mark having the vias 16 formed therein undergoes processes such as photolithography and plating (copper plating, etc.) to form a conductive layer (not shown) on the wiring 7 exposed from the vias 16, and is mounted and joined to an electronic device or electronic component. The electronic device or electronic component is electrically connected to the wiring 7 through the vias 16.

[0123] <Effects of one embodiment> Since the marked laminated sheet 1 has the marks 4, the marked laminated sheet 1 can be aligned based on the marks 4 to form the vias 16.

[0124] Furthermore, since the marked laminated sheet 1 includes the mark layer 3, the mark 4 can be reliably provided.

[0125] Although not shown, if the mark 4 is disposed facing one side of the wiring 7 in the thickness direction, the mark 4 may be misaligned due to the presence of the wiring 7.

[0126] However, in this laminated sheet 1 with marks, the marks 4 are spaced apart from the wiring 7. In other words, the marks 4 are not disposed facing one side of the wiring 7 in the thickness direction. Therefore, the marks 4 are formed without misalignment caused by the presence of the wiring 7. This allows the laminated sheet 1 with marks to be aligned even more accurately.

[0127] Furthermore, in this marked laminate sheet 1, if the material of the mark layer 3 is a resin composition, the marks 4 can be easily formed.

[0128] <Modification> In the following modifications, the same components and steps as those in the above-described embodiment are denoted by the same reference numerals, and detailed description thereof will be omitted. In addition, each modification can achieve the same effects as those in the above-described embodiment, unless otherwise specified. Furthermore, the embodiment and its modifications can be appropriately combined.

[0129] The shape of the mark 4 is not limited to the above. Although not shown, examples of the shape of the mark 4 in plan view include a substantially V-shape, a substantially X-shape, a substantially L-shape, a substantially I-shape (including a substantially linear shape), a substantially U-shape, a substantially C-shape, a substantially annular shape (including a substantially elliptical annular shape), a substantially circular shape (including a substantially elliptical shape), a substantially polygonal frame shape (including a substantially triangular frame shape and a substantially rectangular frame shape), and a substantially polygonal shape (including a substantially triangular shape and a substantially rectangular shape).

[0130] The position of the mark 4 is not particularly limited, and may be, for example, between adjacent wirings 7, although not shown.

[0131] As shown in FIG. 3, the markable layer 15 may be a laser-changeable layer and / or an ink-receptive layer.

[0132] When the mark-formable layer 15 is a laser-discolorable layer, both the laser-discolorable layer and the mark layer 3 contain, for example, a thermosetting resin as the resin and spherical carbon black as the first particles, and have, for example, a black color. When the laser-discolorable layer is irradiated with a laser, the first particles (carbon black) in the irradiated portion are thermally decomposed and removed, and the blackness of the portion decreases (the color becomes lighter) (the color changes). As a result, the mark-formable layer 15 becomes the mark layer 3 having the discolored mark 4.

[0133] When the mark-formable layer 15 is an ink-receiving layer, the ink-receiving layer and the mark layer 3 contain, for example, a hydrophilic polymer as a resin and spherical silica as a first particle. Ink (not shown) is printed on the mark-formable layer 15, and then the hydrophilic polymer and silica of the mark-formable layer 15 absorb (have affinity with) the ink. As a result, the mark-formable layer 15 becomes the mark layer 3 having the colored marks 4.

[0134] As shown in FIG. 4, the mark 4 may be a through hole penetrating the mark layer 3 .

[0135] 5, the mark 4 may be disposed on one surface in the thickness direction of the mark layer 3. The mark 4 is made of, for example, a solid ink (preferably a cured product such as an ultraviolet cured product).

[0136] 6 to 8, the marks 4 can also be formed directly on the inductor 2, rather than on the mark layer 3. In this modification, the inductor 2 and the marks 4 are provided in a marked inductor 21. More specifically, the marked inductor 21 does not include a mark layer 3, and includes only the inductor 2 and the marks 4. The marked inductor 21 is not a marked laminated sheet 1.

[0137] In a modified inductor 21 with marks shown in Fig. 6, the marks 4 are formed on one surface 9 of the inductor 2. The marks 4 are magnetic recesses 26 extending from one surface 9 of the magnetic layer 8 toward the other side, halfway through the thickness direction. The dimensions of the magnetic recesses 26 in a plan view are similar to the dimensions of the marks 4 in the embodiment.

[0138] 7, the mark 4 is a through hole 27 that penetrates the inductor 2 in the thickness direction. More specifically, the through hole 27 penetrates the magnetic layer 8 in the thickness direction. The dimensions of the through hole 27 in a plan view are similar to the dimensions of the mark 4 in the embodiment.

[0139] Methods for forming the magnetic recess 26 shown in Fig. 6 and the through hole 27 shown in Fig. 7 include contact processing such as drilling and sandblasting, and non-contact processing using a laser, for example. Contact processing is preferred because it requires a short processing time, and drilling is more preferred.

[0140] For example, an insulating layer 28 shown by a virtual line can be disposed on one surface 9 in the thickness direction of the magnetic layer 8 shown in Figs. 6 and 7. The insulating layer 28 contacts one surface 9 in the thickness direction of the magnetic layer 8. The insulating layer 28 extends in the planar direction. Examples of materials for the insulating layer 28 include the resin compositions exemplified as the materials for the mark layer 3 in one embodiment. In Fig. 6, the insulating layer 28 fills the magnetic recesses 26. In Fig. 7, the insulating layer 28 closes one edge in the thickness direction of the through hole 27. Although not shown, the through hole 27 may be filled with the resin composition used for the insulating layer 28.

[0141] Comparing the magnetic recess 26 shown in Fig. 6 with the through hole 27 shown in Fig. 7, the through hole 27 shown in Fig. 7 is preferable. With the modified example of Fig. 7, visibility from the other side in the thickness direction can be ensured when the insulating layer 28 shown by the imaginary line is formed.

[0142] Although not shown, the mark 4 can be provided on both the mark layer 3 and the inductor 2 .

[0143] In a modified marked inductor 21 shown in Fig. 8, the mark 4 is formed by cutting out a corner 6 (see Fig. 6) of the inductor 2. The mark 4 is formed by cutting out the corner 6 in a rectangular shape in the thickness direction.

[0144] 9, the mark 4 may include information about the marked laminate sheet 1 (or the marked inductor 21) as a product instead of or together with the alignment mark. Examples of the information include the lot number of the marked laminate sheet 1, the magnetic permeability of the marked laminate sheet 1, etc.

[0145] As shown by the dashed-dotted line in Fig. 2B, the mark-formable layer 15 can also be formed on one surface 9 and the other surface 10 of the inductor 2. In this modification, as shown in Fig. 2C, two mark layers 3 are disposed on each of the one surface 9 and the other surface 10. A mark 4 is formed on each of the two mark layers 3.

[0146] The modified example in which the marks 4 are formed on each of the two mark layers 3 is preferable compared to the embodiment in which the marks 4 are formed on only one mark layer 3 in the following respects.

[0147] In the case where it is necessary to form vias 16 from both sides in the thickness direction of the marked laminated sheet 1, in the above-mentioned modified example, the surface on which the vias 16 are formed and the surface on which the marks 4 are recognized can be made the same surface. This improves manufacturing efficiency. On the other hand, when the vias 16 are formed on one surface 9 and the marks 4 are formed on the other surface 10, that is, when the surface on which the vias 16 are formed and the surface on which the marks 4 are recognized are on different surfaces, it is necessary to turn the marked laminated sheet 1 over in the thickness direction or to recognize the marks 4 from the other side in the thickness direction, which makes the process of forming the vias 16 very complicated.

[0148] By changing the shape and / or formation method of the marks 4 on one side in the thickness direction from the marks 4 on the other side, both sides in the thickness direction of the marked laminated sheet 1 can be easily and reliably identified.

[0149] When it is necessary to provide a large number of marks 4, it is possible to effectively utilize the spaces on both sides in the thickness direction of the marked laminated sheet 1. In other words, when there is little free space on only one side in the thickness direction, the other side can be effectively utilized.

[0150] If the position of the mark 4 on one side in the thickness direction and the position of the mark 4 on the other side are the same when projected in the thickness direction, but their shapes are different, a recognition device (e.g., an X-ray recognition device) that uses energy rays that penetrate the marked laminated sheet 1 can be used to obtain two pieces of information in one recognition process (imaging), thereby improving manufacturing efficiency.

[0151] The marked laminate sheet 1 can be obtained by cutting a second marked laminate sheet (not shown) that is larger in size in a plan view than the marked laminate sheet 1. The second marked laminate sheet has a plurality of areas (not shown) corresponding to the marked laminate sheet 1 before cutting. Each of the plurality of areas is provided with a mark 4. The second marked laminate sheet (not shown) is cut using the mark 4 to obtain a plurality of individualized marked laminate sheets 1. Vias 16 can be provided in each of the plurality of areas of the second marked laminate sheet (not shown). The mark 4 is read by a cutting device to identify the area corresponding to the marked laminate sheet 1, and the second marked laminate sheet (not shown) is cut into individual pieces. Both the marked laminate sheet 1 and the second marked laminate sheet (not shown) are included in the marked laminate sheet of the present invention.

[0152] The marked inductor 21 can be obtained by cutting a second marked inductor (not shown) that is larger in size in a plan view than the marked inductor 21. The second marked inductor has a plurality of areas (not shown) that correspond to the marked inductor 21 before cutting. Each of the plurality of areas is provided with a mark 4. The second marked inductor (not shown) is cut using the mark 4 to obtain a plurality of individualized marked inductors 21. The mark 4 is read by a cutting device to identify the area corresponding to the marked inductor 21, and the second marked inductor (not shown) is cut and individualized. Both the marked inductor 21 and the second marked inductor (not shown) are included in the marked inductor of the present invention. [Explanation of symbols]

[0153] 1. Marked laminated sheet 2 Inductors 4 Marks 7 Wiring 8 Magnetic layer 21 Marked inductor 27 Through hole

Claims

1. a sheet-like inductor including a plurality of wirings and a magnetic layer in which the plurality of wirings are embedded; a mark disposed on one side in a thickness direction of the inductor and / or formed on the magnetic layer; A marked inductor comprising:

2. The inductor with a mark according to claim 1 , wherein the mark is spaced apart from the wiring when projected in a thickness direction.

3. 3. The inductor with a mark according to claim 1, wherein the mark is disposed on one side of the inductor in a thickness direction; a mark layer on which the mark is arranged, the mark layer being disposed on one surface of the inductor in the thickness direction; A laminated sheet with a mark, comprising:

4. 4. The marked laminate sheet according to claim 3, wherein the mark layer is made of a resin composition.

5. The resin composition is a thermosetting resin composition, 5. The marked laminate sheet according to claim 4, which satisfies at least one of the following tests (a) to (e): Test (a): The laminated sheet with the mark is processed to a 3 cm square to prepare a sample, and its relative permeability μ1 at a frequency of 10 MHz is determined. The sample is then immersed in 200 mL of a copper sulfate plating solution containing 66 g / L of copper sulfate pentahydrate, 180 g / L of sulfuric acid, 50 ppm of chlorine, and top lutina α at 25° C. for 120 minutes, and then the relative permeability μ2 at a frequency of 10 MHz of the sample is determined. The rate of change in permeability before and after immersion is determined using the following formula. As a result, the rate of change in permeability of the sample is 5% or less. Permeability change rate (%) = |μ1-μ2| / μ1×100 Test (b): The marked laminated sheet is cut into a 3 cm square to prepare a sample, and its relative permeability μ3 at a frequency of 10 MHz is measured. The sample is then immersed in 200 mL of an acid activation aqueous solution containing 55 g / L of sulfuric acid at 25° C. for 1 minute, and the relative permeability μ4 at a frequency of 10 MHz is measured. The rate of change in permeability before and after immersion is calculated using the following formula. As a result, the rate of change in permeability of the sample is 5% or less. Permeability change rate (%) = |μ3 - μ4| / μ3 × 100 Test (c): The laminated sheet with the mark is cut into a 3 cm square to prepare a sample, and the relative permeability μ5 at a frequency of 10 MHz is measured. The sample is then immersed in 200 mL of Reduction Solution Securigant P manufactured by Atotech Japan at 45° C. for 5 minutes, and the relative permeability μ6 at a frequency of 10 MHz is then measured. The rate of change in magnetic permeability before and after immersion is calculated using the following formula: As a result, the rate of change in magnetic permeability of the sample is 5% or less. Permeability change rate (%) = |μ5-μ6| / μ5×100 Test (d): The laminated sheet with the mark is cut into a 3 cm square to prepare a sample, and its relative magnetic permeability μ7 at a frequency of 10 MHz is measured. The sample is then immersed in 200 mL of Concentrate Compact CP manufactured by Atotech Japan at 80° C. for 15 minutes, and the relative magnetic permeability μ8 at a frequency of 10 MHz is then measured. The rate of change in magnetic permeability before and after immersion is calculated using the following formula. As a result, the rate of change in magnetic permeability of the sample is 5% or less. Permeability change rate (%) = |μ7 - μ8| / μ7 x 100 Test (e): The laminated sheet with the mark is cut into a 3 cm square to prepare a sample, and its relative magnetic permeability μ9 at a frequency of 10 MHz is measured. The sample is then immersed in 200 mL of Swelling Dip Securigant P manufactured by Atotech Japan at 60° C. for 5 minutes, and the relative magnetic permeability μ10 at a frequency of 10 MHz is then measured. The rate of change in magnetic permeability before and after immersion is calculated using the following formula. As a result, the rate of change in magnetic permeability of the sample is 5% or less. Permeability change rate (%) = |μ9 - μ10| / μ9 × 100

6. The mark is a through hole that penetrates the magnetic layer in the thickness direction.

2. The marked inductor according to claim 1 .

Citation Information

Patent Citations

  • inductor

    JP2019220618A